Deficiency of the Cog8 Subunit in Normal and CDG‐Derived Cells Impairs the Assembly of the COG and Golgi SNARE Complexes. (31st July 2013) - Laufman, Orly; Freeze, Hudson H.; Hong, Wanjin; Lev, Sima
<x xml:space="preserve">Abstract</x> Cog8 is required for the assembly of the COG complex and the Golgi Stx5‐GS28‐Ykt6‐GS15 and Stx6‐Stx16‐Vti1a‐VAMP4 SNARE complexes in HeLa cells and CDG‐derived fibroblasts. The assembly of these SNARE complexes is also impaired in Cog7‐deficient CDG‐derived cells. Deficiency of Cog1, Cog4, Cog6 or Cog8 disrupts the COG complex integrity, but distinctly influences the assembly of COG subcomplexes and their Golgi localization. These differences may distinctly influence the two major COG functions in tethering and SNAREpin assembly, thereby exerting multiple phenotypes.<boxed-text content-type="graphic" id="tra12093-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>